Chromatin Accessibility and Interactions in the Transcriptional Regulation of T Cells - Li, Peng; Leonard, Warren J. (Frontiers in Immunology, 2018)
During T cell differentiation and activation, specific stimuli and a network of transcription factors are involved in orchestrating chromatin accessibility, establishing enhancer-promoter interactions, and regulating gene expression. Over the past few years, there have been new insights into how chromatin interactions coordinate differentiation during T cell development and how regulatory elements are programmed to allow T cells to differentially respond to distinct stimuli. In this review, we discuss recent advances related to the roles of transcription factors in establishing the regulatory chromatin landscapes that orchestrate T cell development and differentiation. In particular, we focus on the role of transcription factors (e.g., TCF-1, BCL11B, PU.1, STAT3, STAT5, AP-1, and IRF4) in mediating chromatin accessibility and interactions and in regulating gene expression in T cells, including gene expression that is dependent on IL-2 and IL-21. Furthermore, we discuss the state of knowledge on enhancer-promoter interactions and how autoimmune disease risk variants can be linked to molecular functions of putative target genes.